2011
DOI: 10.1111/j.1365-2435.2010.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing stomatal conductance for maximum carbon gain under water stress: a meta-analysis across plant functional types and climates

Abstract: Summary1. Quantification of stomatal responses to environmental variables, in particular to soil water status, is needed to model carbon and water exchange rates between plants and the atmosphere. 2. Models based on stomatal optimality theory successfully describe leaf gas exchange under different environmental conditions, but the effects of water availability on the key optimization parameter [the marginal water use efficiency (WUE), k = ¶A ⁄ ¶E] has resisted complete theoretical treatment. Building on previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
205
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(218 citation statements)
references
References 69 publications
12
205
1
Order By: Relevance
“…Early planting in 2014/15 and mid planting in 2015/16 seasons experienced sufficient distribution of rainfall majorly in their growth and developmental stages which enhanced stomatal conductivity. Manzoni et al (2011) reported that high stomatal increased CO 2 diffusion inside the leaf thus improving photosynthetic rate. Low stomatal conductivity in late planting at both seasons might be due to stomatal closure which is widely thought to be plant's first line of defence in response to developing water stress.…”
Section: Discussionmentioning
confidence: 99%
“…Early planting in 2014/15 and mid planting in 2015/16 seasons experienced sufficient distribution of rainfall majorly in their growth and developmental stages which enhanced stomatal conductivity. Manzoni et al (2011) reported that high stomatal increased CO 2 diffusion inside the leaf thus improving photosynthetic rate. Low stomatal conductivity in late planting at both seasons might be due to stomatal closure which is widely thought to be plant's first line of defence in response to developing water stress.…”
Section: Discussionmentioning
confidence: 99%
“…C 4 crops are generally found to have high phosphoenolpyruvate carboxylase activity (Still et al, 2003). In addition, many studies have found that C 4 plants exhibited increasing WUE in response to rising CO 2 with reductions in stomatal conductance and transpirational water loss compared to C 3 species (Manzoni et al, 2011;Traore et al, 2014). Nevertheless, WUE RS only captured the broad trend of WUE.…”
Section: Comparisons Of Wue From Flux Tower Measurements and Modis Esmentioning
confidence: 99%
“…Our results indicate that the combined effects of soil moisture and atmospheric drought on stomatal conductance have to be taken into account. Moreover, model performance could be improved through the inclusion of non-stomatal limitations on plant photosynthesis, which have been considered to be important for the simulation of short-term plant responses to drought (Egea et al, 2011;Manzoni et al, 2011;Zhou et al, 2013). However, JSBACH is being continuously developed and the effect of soil water stress is to be accounted for according to Egea et al (2011) for both stomatal and nonstomatal processes, affecting both conductance and photosynthesis parameters.…”
Section: Differences Between Observations and Site Simulationsmentioning
confidence: 99%